On Local Separation of Processing and Storage in Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 9th International Conference, GECON 2012, Berlin, Germany, November 27-28, 2012. Proceedings)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks, Workshop Proceedings, Clearwater Beach, FL, USA, October 22-25, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)

Using OMNeT++ for energy optimization simulations in mobile core networks - Dräxler, Martin; Beister, Frederic; Kruska, Stephan; Aelken, J.; Karl, Holger (International ICST Conference on Simulation Tools and Techniques, SIMUTOOLS '12, Sirmione-Desenzano, Italy, March 19-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Queuing Latency at Cooperative Base Stations - Hohenberger, Till

Optimale Zuteilung von Nutzern zu verteilten Cloud-Standorten - Rojahn, Tobias

Introducing feedback to preemptive routing and wavelength assignment algorithms for dynamic traffic scenarios - Wette, Philip; Karl, Holger
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to setup a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known by the RWA algorithm. Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parameters only known at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason a RWA algorithm is needed which involves its users in the preemption decisions. We present a family of preemptive RWA algorithms for WDM networks. These algorithms have two distinguishing features: a) they can handle dynamic trafﬁc by on-the-ﬂy reconﬁguration, and b) users can give feedback for reconﬁguration decisions and thus inﬂuence the preemption decision of the RWA algorithm, leading to networks which adapt directly to application needs. This is different from trafﬁc engineering where the network is (slowly) adapted to observed trafﬁc patterns. Our algorithms handle various WDM network conﬁgurations including networks consisting of heterogeneous WDM hardware. To this end, we are using the layered graph approach together with a newly developed graph model that is used to determine conﬂicting lightpaths.